Technical efficiency of insecticides against Helicoverpa armigera Hübner caterpillars in corn crops - Liaska, Yu. (Quarantine and plant protection, 2023)
Goal. To establish the effectiveness of the use of modern insecticides in corn crops against the cotton bollworm. Methods. Determination of the technical efficiency of insecticides was carried out in field conditions. Treatment with chemical insecticides was carried out on the 3rd day after the mass flight of H. armigera once, with biological preparations — twice, during the period of mass revival of caterpillars. Observation of the pest after treatment with drugs was carried out on the 3rd, 7th and 14th day at the rate of ex./100 plants in four repetitions, by counting them on cobs, panicles and leaves. For the experiments, the Paradiz corn hybrid (mid-early) was used, the seeds of which were pre-treated at the plant with a fungicide Maksym XL 035 FS (fludioxonil, 25 g/l, metalaxyl-M, 10 g/l) — 1 l/t. The beginning and intensity of the flight of cotton bollworm adults was determined using pheromone traps. The collection of male imagos was carried out every three days after the start of the flight. Data on crop losses were based on the actually calculated indicators of each variant of the experiment. The reliability of the obtained results was determined using the mathematical and statistical method. Results. In 2021—2022, when testing insecticides against cotton bollworm caterpillars on corn crops, the highest technical efficiency was provided by: Koragen 20 KS (chlorantraniliprole, 200 g/l) — 82.1% and Ampliho 150 ZC, FC (chlorantraniliprole 150 g/l, lambda-cyhalothrin 50 g/l) — 77.7%. The biological preparations of Lepidotsyd-BTU, r. (Bacillus thuringiensis var. Kurstaki, serotype 3, titer 1.0 ќ 10 9 CFU/cm3) had the lowest technical efficiency — 48.2% and Bitoksybatsylin-BTU, r. (Bacilius thuringiensis var Thuringiensis, endospores — titer 1.0 ќ 10 9 CFU/ cm3) — 53.7%. When using the tested insecticides, the productivity of the Paradiz hybrid was higher compared to the control. When treated with Koragen 20 KS and Ampligo 150 ZC, FC, the yield increased by 0.480 and 0.320 t/ha. When treated with Radiant, CS (spinetoram, 120 g/l) and Belt 480 SC, CS (flubendiamide, 480 g∕l), — by 0.250 and 0.280 t/ha, respectively more. With the use of Liufoks 105 ES, e.c. (75 g/l fenoxycarb, 30 g/l lufenuron), Lepidotsyd-BTU, r. and Bitoksybatsylin-BTU, r., the amount of preserved corn grain yield was 0.190, 0.110 and 0.140 t/ha, respectively. Conclusions. It was found that Koragen 20 KS (82.1%) and Ampligo 150 ZC, FK (7.7%) were the most effective insecticides against cotton bollworm caterpillars in the Left Bank Forest Steppe of Ukraine. The specified drugs are used in low concentrations, and with the help of phytosanitary and instrumental monitoring in corn crops, treatment is recommended to be carried out once, which in turn allows to reduce the pesticide load on the ecosystem and prevents the development of resistance in phytophagous plants.